2015
DOI: 10.14202/vetworld.2015.1340-1345
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical studies in experimentally Escherichia coli infected broiler chicken supplemented with neem (Azadirachta indica) leaf extract

Abstract: Aim: An experimental study was conducted on 192-day-old broiler chicks for evaluating the effect of 10% neem leaf extract (NLE) supplementationon biochemical parameters in chickens experimentally infected with Escherichia coli O78 at 10 7 CFU/0.5 ml at 7 days of age. Materials and Methods:The 192-day-old broiler chicks were procured. These chicks were divided into two groups (A and B) containing 96 birds each on the 1 st day. Diet of all the chicks of Group A was supplemented with 10%NLE in water, whereas chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
5
19
0
2
Order By: Relevance
“…While the infected and treated groups with Yeast and Sangrovit showed a significant decrease compared to the infected group. These results were in agreement with Madian et al, (2008); Sharma et al, (2015) and Fatma (2005) who found that the levels of ALT and AST were significantly increased in E.coli infected broilers as compared to control. These elevations due to hepatocellular damage caused by E.coli.…”
Section: Resultssupporting
confidence: 92%
“…While the infected and treated groups with Yeast and Sangrovit showed a significant decrease compared to the infected group. These results were in agreement with Madian et al, (2008); Sharma et al, (2015) and Fatma (2005) who found that the levels of ALT and AST were significantly increased in E.coli infected broilers as compared to control. These elevations due to hepatocellular damage caused by E.coli.…”
Section: Resultssupporting
confidence: 92%
“…In the present study, E. coli infection occurred colibacillosis infection, which indicated by results of E. coli colonization and increased serum biochemical parameters. In addition, Sharma et al [19] reported that the increase in serum activities of ALT is indicative of cellular injury to hepatocytes and AST in cardiac muscles and hepatocytes as well. On the other hand, hypoproteinemia may be due to hepatocyte damage, which results in failure in the synthesis of plasma protein, where the liver is a site for albumin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hypoproteinemia may be due to hepatocyte damage, which results in failure in the synthesis of plasma protein, where the liver is a site for albumin synthesis. Also, hypoproteinemia may be due to kidney disease, which leads to protein loss and congestive heart failure [19,20]. At the same time, hyperglobulinemia is associated with liver cirrhosis, hepatitis, and Kuffer cell proliferation [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adult birds salpingitis, ovaritis and yolk peritonitis [7][8][9][10] were found. Pathological and anatomical changes in farm animals with colibacteriosis have received extensive coverage in the literature viz., in poultry [11], rabbit [12], donkey [13], broiler chicken [14], human and calves [15]. However, research works focused on the study of synanthropic birds, in particular pigeons, which play a key role in the spread of colibacteriosis in cities, were of a single nature.…”
Section: Translational Research In Veterinary Sciencementioning
confidence: 99%